Novel insights in pathophysiology of antiblastic drugs-induced cardiotoxicity and cardioprotection. (May 2016) - Deidda, Martino; Madonna, Rosalinda; Mango, Ruggiero; Pagliaro, Pasquale; Bassareo, Pier P.; Cugusi, Lucia; Romano, Silvio; Penco, Maria; Romeo, Francesco; Mercuro, Giuseppe
Abstract : Despite advances in supportive and protective therapy for myocardial function, heart failure caused by various clinical conditions, including cardiomyopathy due to antineoplastic therapy, remains a major cause of morbidity and mortality. Because of the limitations associated with current therapies, investigators have been searching for alternative treatments that can effectively repair the damaged heart and permanently restore its function. Damage to the heart can result from both traditional chemotherapeutic agents, such as anthracyclines, and new targeted therapies, such as trastuzumab. Because of this unresolved issue, investigators are searching for alternative therapeutic strategies. In this article, we present state-of-the-art technology with regard to the genomic and epigenetic mechanisms underlying cardiotoxicity and cardioprotection, the role of anticancer in influencing the redox (reduction/oxidation) balance and the function of stem cells in the repair/regeneration of the adult heart. These findings, although not immediately transferable to clinical applications, form the basis for the development of personalized medicine based on the prevention of cardiotoxicity with the use of genetic testing. Proteomics, metabolomics and investigations on reactive oxygen species-dependent pathways, particularly those that interact with the production of NO and energy metabolism, appear to be promising for the identification of early markers of cardiotoxicity and for the development of cardioprotective agents. Finally, autologous cardiac stem and progenitor cells may represent future contributions in the field of myocardial protection and recovery in the context of antiblastic therapy.